miR-204-5p inhibits proliferation and invasion and enhances chemotherapeutic sensitivity of colorectal cancer cells by downregulating RAB22A - Yin, Yuan; Zhang, Binbin; Wang, Weili; Fei, Bojian; Quan, Chao; Zhang, Jiwei; Song, Mingxu; Bian, Zehua; Wang, Qifeng; Ni, Shujuan; Hu, Yaling; Mao, Yong; et al. (Clinical cancer research, 2014)
miR-204-5p was found to be downregulated in colorectal cancer tissues in our preliminary microarray analyses. However, the function of miR-204-5p in colorectal cancer remains unknown. We therefore investigated the role, mechanism, and clinical significance of miR-204-5p in colorectal cancer development and progression. We measured the expression of miR-204-5p and determined its correlation with patient prognoses. Ectopic expression in colorectal cancer cells, xenografts, and pulmonary metastasis models was used to evaluate the effects of miR-204-5p on proliferation, migration, and chemotherapy sensitivity. Luciferase assay and Western blotting were performed to validate the potential targets of miR-204-5p after the preliminary screening by a microarray analysis and computer-aided algorithms. miR-204-5p is frequently downregulated in colorectal cancer tissues, and survival analysis showed that the downregulation of miR-204-5p in colorectal cancer was associated with poor prognoses. Ectopic miR-204-5p expression repressed colorectal cancer cell growth both in vitro and in vivo. Moreover, restoring miR-204-5p expression inhibited colorectal cancer migration and invasion and promoted tumor sensitivity to chemotherapy. Mechanistic investigations revealed that RAB22A, a member of the RAS oncogene family, is a direct functional target of miR-204-5p in colorectal cancer. Furthermore, RAB22A protein levels in colorectal cancer tissues were frequently increased and negatively associated with miR-204-5p levels and survival time. Our results demonstrate for the first time that miR-204-5p acts as a tumor suppressor in colorectal cancer through inhibiting RAB22A and reveal RAB22A to be a new oncogene and prognostic factor for colorectal cancer.